Metastatic Phyllodes Tumor in a Patient With Beckwith-Wiedemann Syndrome - Astha Saini DO; Trisha Gupte BS; Moumita S. R. Choudhury MD; Suzanne M. Jacques MD; Renato Roxas MD (SAGE Publishing, 2022)
Beckwith-Wiedemann syndrome (BWS) is an epigenetic disorder of imprinting on the chromosome 11p15 region that presents with clinical features, such as macroglossia, abdominal wall defects, neonatal hypoglycemia, hemihypertrophy, and embryonal tumors. Phyllodes tumors (PTs) are rare fibroepithelial tumors that account for 0.3% to 1% of breast tumors and present in women aged 35 to 55 years. Here we describe a rare case of metastatic malignant phyllodes tumor in a 27-year-old woman with BWS and uniparental disomy (UPD) of chromosome 11p15.5. To our knowledge, this is the first case report in literature to describe metastatic malignant phyllodes tumor in a woman with BWS.